Efficacy of Paclitaxel Combined with Kanglaite Injection in Treatment of Bone Metastases of Lung Cancer - Liming CAO; Long LONG; Chengping HU (Tehran University of Medical Sciences, 2019)
Background: We aimed to investigate the efficacy of paclitaxel combined with kanglaite injection in the treatment of bone metastases of lung cancer in mice. Methods: Human lung cancer cell line A549 was inoculated into 100 C57BL/6 mice to establish bone metastasis model of lung cancer. Eighty successful modeling mice were randomly divided into four groups: Kanglaite (group A), Paclitaxel (group B), Paclitaxel combined with kanglaite (group C) and 0.9% sodium chloride solution (control group), 20 in each group. The mice started taking drugs on the 5th day after inoculation. The treatment lasted for 21 days, and the changes of body weight were observed. Evaluation of the efficacy of drug therapy was performed by comparing the pain behavior of the treated mice with that of the control mice. Results: The physical improvement rates in group A and group B were lower than that in group C (P<0.05). The bone metastasis area and tumor weight in group A, group B and group C were significantly lower than those in control group after 21 days of treatment (P<0.05). The tumor area and tumor weight in group C were significantly lower than those in group A and group B (P<0.05). Conclusion: Paclitaxel combined with kanglaite is more effective than paclitaxel or kanglaite alone in improving bone metastasis of lung cancer and has an important significance in clinical treatment of bone metastasis of lung cancer.